A COMPARATIVE CRIMINAL LAW ANALYSIS OF SEXUAL VIOLENCE WITHIN DOMESTIC CONTEXTS: PERSPECTIVES FROM INDONESIA AND MALAYSIA - Purnamasari, Rycha Widy; Widoyoko, Wredha Danang (jfpublisher, 2025)
This research addresses domestic sexual violence as a hidden crime where victims choose not to report due to family disgrace concerns, causing high dark numbers. The study employs a normative legal research methodology, utilizing various legal materials including laws, court decisions, and legal theories through comparative and statutory approaches to analyze Indonesian and Malaysian criminal law frameworks. The research reveals that Malaysian law classifies sanctions for domestic sexual violence suspects based on victim categorization, whereas Indonesian law lacks such classification systems for sanctions against suspects based on their victims. However, Indonesia explicitly regulates who is protected by law and applies much more severe sanctions against domestic sexual violence perpetrators compared to Malaysian criminal law. The findings demonstrate that based on joint punishment theory, sanctions applied to domestic sexual violence perpetrators must serve dual purposes as deterrent and deterrence effects, intended to prevent perpetrators and potential offenders from repeating such crimes. This comparative analysis contributes novel insights into the differential approaches between Indonesian and Malaysian legal systems in addressing domestic sexual violence, highlighting Indonesia's more comprehensive punitive framework while identifying Malaysia's victim-based classification system as a distinctive feature in determining appropriate sanctions for domestic sexual violence cases.